Inventory Information System using Technique of Data Mining Companies Warehousing - Indiharto, Raden Adhiyaksa; Hilda, Atiqah Meutia; Mintarsih, Fitri (POLITEKNIK NEGERI JAKARTA, 2016)
The mechanism of procurement of goods that were done manually, but now it can be facilitated by the existence of web-based procurement system. This system is designed using the data mining technique to find any parts of the goods data that often requested based on a monthly period/year and knowing the type of goods are the most requested and the most frequently consumed the preparation. This research uses a decision tree method and CARTS (Classifcation and Regression Tree) algorithm for exploring the data. The design method of this system using object-oriented development with UML modeling system. Inventory information system software is used to facilitate the process of procurement of goods and the existing equipment on the warehousing company multi-user web-based by the mechanisms of the process of the administration and procurement of goods made online. This application is supporting the administration process of procurement of goods in each company warehouse. This application is equipped with features to request the procurement of goods, maintenance procurement of goods and procurement of goods online report. The purpose of this research is to produce a web-based inventory information system that make easier and speed up the process of inventory and procurement of goods in a company warehouse